Adjuvant modulation of the immune response of mice against the LcrE protein of Chlamydophila pneumoniae - Faludi Ildikó (INTERNATIONAL JOURNAL OF MEDICAL MICROBIOLOGY, 2009)
LcrE protein is a TTSS component of Chlamydophila pneumoniae. The immunogenicity and protective effect of recombinant LcrE protein combined either with Freund's or Alum adjuvant were investigated in mice. The immunization with both protocols resulted in a significant reduction of the number of viable C pneumoniae in the lungs after challenge. Lower IgG2a/IgG1 ratio in Alum-immunized mice suggested a shift towards Th2 type immune response, but the presence of LcrE-specific IFN-gamma-producing cells in LcrE+Alum-immunized mice also indicates Th1 type response. LcrE-specific IgA level was higher in both the sera and the lungs after using Freund's adjuvant. Phenotype of LcrE-specific IFN-gamma-producing cells was CB4+ in Alum- and Freund's-immunized mice, but CD8+ cells were also detected in Freund's-immunized mice. These results confirm that LcrE induces protective immunity in mice. The results also show that Alum is able to activate the CD4+ cell-based cellular immunity, thus it can be regarded as an alternative adjuvant during vaccine screening and a useful adjuvant in a potential protein vaccine against C. pneumoniae infection. (C) 2009 Elsevier GmbH. All rights reserved.